A Model for the Development of the Teaching Efficiency of Religious Teachers in Islamic Private Schools in the Three Southernmost Provinces of Thailand - Churngchow, Chidchanok; Rorbkorb, Narongsak; Petch-urai, Ontip; Chirtkiatsakul, Busaban; Waedramae, Mahdee; Saneeyeng, Rohana; Aumchoowattana, Yupawat (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The purpose of this research was to develop a model to improve the teaching efficiency of religious teachers in Islamic private schools in the three southernmost provinces of Thailand using mixed research methods in an exploratory sequential design. Results showed that all six components of teacher efficiency were at unacceptable level and need to be improved urgently. In addition, an institution which has the specific purpose of improving the teaching efficiency of religious teachers should be established under the administration of all stakeholders in the region.